Examining the interconnection between maqasid al-shariah and sleep quality - Mohd Amzari Tumiran; Durriyyah Sharifah Hasan Adli; Ahmed Salem Bahammam; Mohd Yakub@Zulkifli Mohd Yusoff (Universiti Sains Islam Malaysia, 2025)
Ulum Islamiyyah, Volume 37 Issue 3 Page (1–18)